Compósito magnético de matriz vítrea bioativa para hipertermia - Santana, Geovana Lira (2020)
Bone cancer is a rare type of neoplasm, but with high rates of new cases annually. With several therapies available for this pathology, a controlled hyperthermia technique is promising. This technique uses the response of a magnetic material to an external magnetic field to generate heat and increase the temperature of the tumor cells, destroying the tumor without killing the neighboring healthy cells. Among the materials used, highlighted as superparamagnetic and ferromagnetic nanoparticles of magnetite. However, magnetite has a high Curie temperature (Tc ~ 580 °C) and its use, it is required a rigorous external temperature control to avoid the local superheating. For this case, a strontium-doped lanthanum manganite (LSM20) has properties capable of replacing magnetite and it shows a Tc within the range of technical application (42-45 °C) being able to self-regulate the temperature. In the present work, we seek to develop a magnetic and bioactive composite with properties capable of being used in bone cancer hyperthermia. The bioactive glass F18 formed a glass matrix with the incorporation of different LSM20 concentrations (5, 10, 20, and 30% by weight). Then, the composites were characterized by magnetic behavior and bioactivity. The results indicate the heating of biocomposites in response to an external magnetic field for all studied compositions, especially those containing 20% and 30% of LSM20, which obtains a temperature increase until close to Tc. Although the presence of LSM20 delayed starting the formation of hydroxycarbonate apatite (HCA), the composites showed bioactive behavior with the creation of HCA in up to 7 days. These magnetic properties and bioactivity of the composites become of great potential for the bone cancer treatment by hyperthermia due to the possible heating control from the stoichiometry of the LSM phase, in the same time, which can keep the magnetic particles fixed to the treatment site through the biocompatibility of the F18 bioactive glass matrix with bone tissue.